Benchmarking and the laboratory. Issue 8 (1st August 2001) - Galloway, M; Nadin, L
Abstract : This article describes how benchmarking can be used to assess laboratory performance. Two benchmarking schemes are reviewed, the Clinical Benchmarking Company's Pathology Report and the College of American Pathologists' Q-Probes scheme. The Clinical Benchmarking Company's Pathology Report is undertaken by staff based in the clinical management unit, Keele University with appropriate input from the professional organisations within pathology. Five annual reports have now been completed. Each report is a detailed analysis of 10 areas of laboratory performance. In this review, particular attention is focused on the areas of quality, productivity, variation in clinical practice, skill mix, and working hours. The Q-Probes scheme is part of the College of American Pathologists programme in studies of quality assurance. The Q-Probes scheme and its applicability to pathology in the UK is illustrated by reviewing two recent Q-Probe studies: routine outpatient test turnaround time and outpatient test order accuracy. The Q-Probes scheme is somewhat limited by the small number of UK laboratories that have participated. In conclusion, as a result of the government's policy in the UK, benchmarking is here to stay. Benchmarking schemes described in this article are one way in which pathologists can demonstrate that they are providing a cost effective and high quality service.